Analisis Perencanaan PPh 21 dengan Metode Gross Up sebagai Upaya Meningkatkan Efisiensi Beban Pajak - Rahmadhani, Cinta Tunggal; Widajantie, Tituk Diah (VISA: Journal of Vision and Ideas, 2025)
This research aims to find out how the company PT XYZ in optimizing the tax burden to reduce risks and avoid tax sanctions by using the Gross-Up method. This method makes the company pay employee taxes, but the employee's net salary remains the same. The research method used in this research is a qualitative descriptive method, namely by studying one case of a company in KKP/KJA Enny Consulting in 2023. The data is analyzed to determine company and employee tax savings after using the Gross-Up method. The results show that this method can save employees taxes and increase their satisfaction. Companies can also manage tax burdens better and according to regulations. This research concludes that the Gross-Up method can be a solution for other companies who want to save PPh 21 taxes for employees and companies.